A global perspective on electrical resistivity tomography, electromagnetic and ground penetration radar methods for estimating groundwater recharge zones - Ali, Nawab; Chappuies, Jack; Sloan, Guy; Rouland, Greg; Rai, Abraham; Dong, Younsuk (Frontiers in Water, 2025)
Accurate estimation of groundwater recharge is crucial for sustainable management of water resources. Various geophysical survey tools are used for groundwater recharge estimation and monitoring of these resources. This paper presents global perspectives of geophysical survey methods such as electrical resistivity tomography (ERT), electromagnetic (EM), and ground penetrating radar (GPR) for groundwater recharge estimation. About 93 papers were screened through PRISMA guidelines and were comprehensively analyzed including statistical metrics, configuration types, geological setting, investigation depth, limitations, and influencing factors. Temperate zones lead in geophysical surveys due to agriculture and interest has risen in mountainous and arid zones. The geological setting also affects the geophysical methods with ERT being the most favorable followed by EM and GPR. Investigation depth and different configurations were also studied. Influencing factors including subsurface heterogeneity and highly conductive soils often reduce resolution and distort signals particularly ERT, EM and GPR in conductive soils. Resistivity and EM measurements are affected by salinity and GPR signals by saturation. Data quality is affected by poor electrode-ground contact, topography, seasonal variability, frequency and cultural noise. Effectiveness and repeatability of geophysical survey methods are influenced by weather conditions and water table depth. Considering these factors, an adaptable and well-planned geophysical survey method selection in diverse geological setting can enhance the precision of groundwater recharge estimation. This paper aims to be the first scoping review on groundwater geophysical survey global perspectives, offering insights for future research.